Can initial perceptions about quitting predict smoking cessation among Malaysian smokers? - Yasin, S.M.; Masilamani, R.; Ming, M.F.; Koh, D.; Zaki, R.A. (2012)
Perceived risks and benefits of quitting smoking may be important factors in successful treatment. This study examined the association between initial perceived risks and benefits of quitting smoking and outcomes during a two month smoking cessation attempt. Participants (n=185) were treatment-seeking smokers attending two smoking cessation clinics in Klang Valley, Malaysia. They received structured behavioral therapy and free Nicotine Replacement Therapy (NRT). Prior to treatment, a 12 item Perceived Risks and Benefits Questionnaire (PRBQ) was administered. This was used to assess the smoker's initial perceptions during their quit attempt. Participants were re-contacted at the end of two months to determine their smoking status. The results show participants intending to quit demonstrated a greater understanding of the benefits of quitting smoking than the risks of quitting. Those with a higher education level had a greater understanding of the benefits of quitting (p=0.02). PRBQ items, such as perceived risks of quitting (ie weight gain, negative affect, social ostracism, loss of enjoyment and craving) were not associated with abstinence at two months. However, those who perceived a benefit of higher physical attraction post-cessation were less likely to have stopped smoking at two months (OR 0.18; 95CI 0.08-0.45). Other perceived benefits at baseline, such as health, general well-being, self-esteem, finances and social approval, were not associated with smoking cessation at two months. The results suggest that in our study population, smokers' baseline perceptions of the benefits of cessation of smoking prior to therapy are not associated with quit results at two months. Counseling patients regarding the advantages and disadvantages of quitting may have changed their perceptions during quitting process and should be further explored in future studies.